STUDI TENTANG NILAI-NILAI PANCASILA YANG TERKANDUNG DALAM TRADISI BAKAR TONGKANG MASYARAKAT TIONGHOA KECAMATAN BANGKO BAGANSIAPIAPI KABUPATEN ROKAN HILIR - ', Jamilah; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is examined based on the pancasila as the outlook of the nation of Indonesia. Pancasila not only as a result of someone or group’s thinking like the other ideology as that be ist in the but also it is as a result which derived from custom, cultural and religious values in Indonesia as incase bakar tongkang tradition which is done continiously from generation of the next the genetation by the Chinese community of Chinese ethnic in bagansiapiapi. The formulation of the problem in this research is whether or not bakar tongkang tradition which is done by Chinese community in bagansiapiapi rokan hilir contains values of pancasila in bagansiapiapi rokan hilir. The purpose of this research is to know the values of pancasila in bakar tongkang tradition in bagansiapiapi. Forthismore, the simle of this research is 30 people of the Chinese community which is selected by using purposive sampling theknique. The data were collected by using Questionare, interviews, views and documentations, the data were analyted by descriptive kualitatife’s formula = P = F/N×100% From research pinding’s. It is found that from 30 respondents who stated there is a values of pancasila in bakar tongkang tradition was 89,5%. Then the people who stated no 9,89%. And not answering 0,61%. So it can be concluded that there is a values of pancasila in bakar tongkang tradition in bagansiapiapi rokan hilir. Key Words: values pancasila, fuel barge traditional Chinese society.